HUBUNGAN DAYA LEDAK OTOT TUNGKAI DAN KOORDINASI MATA-KAKI DENGAN KEMAMPUAN SHOOTING PADA TIM SEPAKBOLA MA AL MUNAWWARAH PEKANBARU - Afrima Deri Deri; Ramadi '; Ardiah Juita Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problem in this study originated from the observation that the researcher found in the field, the deficiencies on the MA Al Munawwarah Pekanbaru football team in doing shot (shooting) while playing. The shooting technique performed is still not perfect, steps and footstool when shooting is not accurate, not done by the explosive power of leg muscle maximally and not accompanied by a balanced coordination between eyes and foot so that the ball does not appropriate to the target. The purpose of this research is to determine the correlation between the explosive power of leg muscle and eyes-foot coordination on the shooting ability at MA Al Munawwarah Pekanbaru football team. The population in this study are MA Al Munawwarah Pekanbaru football team players, up to 18 people by using total sampling technique which all the population are being sampled, so it is not necessary to use t test. To obtain the research data, we used vertical jump test for the explosive power of leg muscle, soccer wall test for eyes-foot coordination and shooting ability test. The data were analyzed with a simple product moment correlation. Based on the analysis of the data obtained correlation X1 with Y are counted rcount =0.530>rtable=0.482 and X2 with Y are counted rcount=0,523>rtable=0.482while the X1 and X2 with Y are counted rcount=0.747>rtable=0.482. Because all of the correlations shown in data analysis are significant, thus Ho is rejected and Ha is accepted. It means that there is a correlation between the explosive power of leg muscle and eyes-foot coordination against shooting ability on the MA Al Munawwarah Pekanbaru football team. Where the provision of a correlation of a variable with other variable is determined by rcount> rtable. Keywords: Explosive Power of Leg Muscle, Eyes-foot coordination, Shooting ability